EPIDERMÓLISE BOLHOSA NA SAÚDE ORAL: MANIFESTAÇÕES CLÍNICAS E ALTERAÇÕES SALIVARES - Azevedo, Brenda Lamonica Rodrigues de (2022)
Epidermolysis bullosa (EB) is an inherited mucocutaneous disease characterized by fragility of the skin and mucous membranes with recurrent blistering. The four main types of EB are simple; junctional; dystrophy and Kindler syndrome. All EB patients can experience oral mucosal lesions such as erythema, ulcer, atrophy and blisters. However, the frequency, extent and severity vary from mild to severe depending on the type of EB. A sociodemographic survey, clinical assessment of the mouth cavity and analysis of aspects related to the saliva of individuals living with EB were carried out and who are followed up at the Blue Butterfly Project of Faculdades Integradas Espírito Santenses (FAESA) and at Hospital Nossa Senhora da Glória. A total of 11 patients (adults and children) diagnosed with EB were part of the sample, of which 27.27% were simple EB, 63.64% recessive dystrophic EB and 9.09% junctional EB. A frequency of 90.90% of patients with recessive dystrophic EB had lesions, while in the junctional EB group it was 9.10%. No patient with simple EB manifested lesions in the oral mucosa. The lesions were similarly distributed between the sexes and the most affected sites were the lips (54%), hard palate (36%) and buccal mucosa (27%). Ankyloglossia, ulcers, blisters and depapilated tongue were more frequently diagnosed. In salivary flow, the intragroup comparison revealed an increase in stimulated collection in relation to passive collection in control subjects (p = 0.0064). In the EB group there was no difference (p = 0.6086). We also did not observe differences in salivary volume between the control and EB groups (p = 0.7117 and p = 0.5557, passive and sti mulated flows respectively). Patients living with EB may have oral lesions, but the recessive dystrophic subtype had a severe clinical picture, with a high rate of mucosal lesions. Regarding salivary flow, it is not clear whether EB individuals are predisposed to manifest hyposalivation. The findings reinforce the need for routine dental follow-up in the multidisciplinary care of individuals living with EB.